PENGARUH KEWIRAUSAHAAN TERHADAP KEMAMPUAN USAHA SERTA KINERJA USAHA RUMAH MAKAN PADANG DI DAERAH ISTIMEWA YOGYAKARTA - Henny Welsa (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
Current number of entrepreneurs in Indonesia is only 0, 18% or about 400.000 people. The number of entrepreneur in USA was 11, 5 % last year and the number of entrepreneur Singapore that had 4,24 million of population in 2005 was 7,2 %. The objectives of this research are to examine the effects entrepreneurship on business competence and performance of Padang Restaurants in special province of Yogyakarta. This study is expected to increase the number of entrepreneurship and is the solution of the unemployment problem in Indonesia is specially in Yogyakarta. 61 respondents from 72 Padang Restaurants. The data were collected using questionnaires and analyzed using Partial Least Square (PLS) analysis. Result of this study proved Ranidar finding (2004) which mentioned that the existence of Padang Restaurants is supported by the power of the norms which is from social and culture of Minang based on Islamic teaching (custom is based on Islam, Islam is based on Holy Quran). This finding also supports the theory of Minang culture. This theory is the concept of life which was prepared Minang’s anchestor for their generation who has purpose to reach a happy and prosperous life in this world and here after. (Idrus, 1998). The business competence has a big role in creating the business perfomance. (Hill and Jones, 1998, Muljadi, 1999). (Kotler 1997). Enterpreneurship depends on the ability of individual to run the business. Meredith et. al., (2000) stated that a person is called enterpreneur if he has an ability to see and find the opportunity and he believes in his own ability to plan, take a risk, inovate, and do some actions to get the goal. The finding of this study is important empirical evidence on the development of the theory and the practice of the enterpreneurship in Indonesia